Rancang Bangun Alat Pendeteksi Banjir Berbasis Arduino Dengan Sensor Untuk Mengurangi Resiko Bencana - Fawwazna, M. Luthfi; Rahman, Riyana; Ramdani, M. Rizki; Fau'din, Ahmad (Yayasan Daarul Huda Kruengmane, 2024)
This research aims to develop a sensor-based flood detection device to increase effectiveness in reducing disaster risk. Floods, as one of the natural disasters that often occur, have the potential to cause significant losses, both in terms of property and loss of life. Therefore, the development of reliable flood detection devices is an urgent need. This research method uses an experimental method involving the use of a number of sensors, such as water level sensors and plans to also install temperature sensors and rainfall sensors, which are integrated into one system. This device is designed to accurately detect changes in environmental conditions that could indicate the potential for flooding. This system is also planned to be equipped with wireless communication technology or an application to provide real-time information to related parties and the public. It is hoped that the implementation of this flood detection device can speed up the response of the authorities and the community in facing potential flood disasters. With the existence of this system, it is hoped that losses due to flooding can be minimized, while strengthening adaptation and disaster risk mitigation capabilities at the local level. This research makes a significant contribution to the development of technology for environmental sustainability and safety.